2014
DOI: 10.1111/acem.12471
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Review and Meta‐analysis of Pregnant Patients Investigated for Suspected Pulmonary Embolism in the Emergency Department

Abstract: In the ED setting, physicians test for PE in pregnant patients at a low threshold, resulting in a low rate of VTE diagnosis and a RR of VTE that is lower than that for nonpregnant women of childbearing age who are tested for PE in the ED setting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
50
0
4

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(54 citation statements)
references
References 56 publications
(103 reference statements)
0
50
0
4
Order By: Relevance
“…The analysis reported by Kline et al 25 and 10 of the studies identified by our review reported the overall prevalence of PE, which was generally found to be low when compared with the non-pregnant population, but did not examine the diagnostic accuracy of clinical features, CDRs or the D-dimer measurement. The remaining seven studies were mostly small and had a low prevalence of PE, and thus had limited power to estimate diagnostic accuracy (especially sensitivity) or detect an association with a reference standard diagnosis of PE.…”
Section: Literature Reviewmentioning
confidence: 86%
See 1 more Smart Citation
“…The analysis reported by Kline et al 25 and 10 of the studies identified by our review reported the overall prevalence of PE, which was generally found to be low when compared with the non-pregnant population, but did not examine the diagnostic accuracy of clinical features, CDRs or the D-dimer measurement. The remaining seven studies were mostly small and had a low prevalence of PE, and thus had limited power to estimate diagnostic accuracy (especially sensitivity) or detect an association with a reference standard diagnosis of PE.…”
Section: Literature Reviewmentioning
confidence: 86%
“…In addition to these studies of pregnant and postpartum women with a suspected PE, Kline et al 25 undertook a systematic review of studies of people with suspected PE, which included pregnant and postpartum women. The authors identified 17 studies including 25,399 patients, of whom 506 (2%) were pregnant, with a 4.1% (95% CI 2.6% to 6.0%) prevalence of PE.…”
Section: Literature Reviewmentioning
confidence: 99%
“…A recent review and meta-analysis showed that the diagnosis of VTE was confi rmed in only 4.1 % of pregnant women, compared with 12.4 % of non-pregnant patients who presented in the emergency unit with the clinical suspicion of PE [103]. To limit the number of radiologic imaging studies in pregnant women, clinical prediction rules, which are an integral part of diagnostic management in the non-pregnant population, might also be desired for pregnant women with suspected VTE.…”
Section: Clinical Pre-test Probabilitymentioning
confidence: 99%
“…A recent meta-analysis demonstrated that this led to a low 4.1% prevalence of VTE among suspected pregnant patients compared with 12.4% in nonpregnant patients. 44 Moreover, many of the common diagnostic tests, including CUS, V-Q lung scan, and CTPA, that have been investigated extensively in nonpregnant patients have not been validated appropriately in pregnancy. Extrapolating results of diagnostic studies of DVT and PE in nonpregnant patients to those who are pregnant may not be correct because of physiologic changes during pregnancy and the possibility of differences in pathophysiology and presentation of VTE in pregnancy.…”
Section: Vte Diagnosis In the Pregnant Patientmentioning
confidence: 99%